Rosuvastatin reduces vascular inflammation and T-cell and monocyte activation in HIV-infected subjects on antiretroviral therapy - Funderburg, Nicholas T; Jiang, Ying; Debanne, Sara M; Labbato, Danielle; Juchnowski, Steven; Ferrari, Brian; Clagett, Brian; Robinson, Janet; Lederman, Michael M; McComsey, Grace A (Journal of acquired immune deficiency syndromes (1999), 2015)
Despite suppressive antiretroviral therapy (ART), increased levels of immune activation persist in HIV-infected subjects. Statins have anti-inflammatory effects and may reduce immune activation in HIV disease. Stopping Atherosclerosis and Treating Unhealthy bone with RosuvastatiN in HIV (SATURN-HIV) is a randomized, double-blind placebo-controlled trial assessing the effect of rosuvastatin (10 mg daily) on markers of cardiovascular risk and immune activation in ART-treated patients. T-cell activation was measured by expression of CD38, HLA-DR, and PD1. Monocyte activation was measured with soluble markers (sCD14 and sCD163) and by enumeration of monocyte subpopulations and tissue factor expression. Markers of systemic and vascular inflammation and coagulation were also measured. SATURN-HIV is registered on clinicaltrials.gov (identifier: NCT01218802). Rosuvastatin, compared with placebo, reduced sCD14 (-10.4% vs 0.5%, P = 0.006), lipoprotein-associated phospholipase A2 (-12.2% vs -1.7%, P = 0.0007), and IP-10 (-27.5 vs -8.2%, P = 0.03) levels after 48 weeks. The proportion of tissue factor-positive patrolling (CD14CD16) monocytes was also reduced by rosuvastatin (-41.6%) compared with placebo (-18.8%, P = 0.005). There was also a greater decrease in the proportions of activated (CD38HLA-DR) T cells between the arms (-38.1% vs -17.8%, P = 0.009 for CD4 cells, and -44.8% vs -27.4%, P = 0.003 for CD8 cells). Forty-eight weeks of rosuvastatin treatment reduced significantly several markers of inflammation and lymphocyte and monocyte activation in ART-treated subjects.